Demographic adversities and Indigenous resilience in Western Alaska - Pratt, Kenneth; Stevenson, Joan; Everson, Phillip (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2013)
Indigenous peoples in the Arctic have historically experienced a broad range of demographic and ecological adversities, the impacts of which sometimes included high mortalities and population dislocations. The anthropological literature has tended to emphasise the dramatic, negative impacts of such events on human groups—to an extent that implies the fabric of social life was typically devastated. This study takes a markedly different perspective by instead describing the resilience of Indigenous populations in the face of culturally traumatic events; in this case, a series of epidemic diseases and major declines in a very critical subsistence resource. Drawing on a rich collection of data documenting Indigenous land use and settlement patterns, the authors explore local responses to significant demographic adversities that befell the people of western Alaska in the 19th and early 20th centuries.